The process of diagnosis of cancer and the effect of the primary care in this process: a single center survey analysis - ÇİFÇİLİ, SALİHA SERAP (My University, 2022)
Background: Cancer diagnosis process can be affected by many factors related to the patient, physician and health system. In order to increase early diagnosis, problems at each step should be determined and precautions should be taken. There are studies showing that cancer misdiagnosis constitutes the majority of diagnostic errors in primary care. In this study, our aim is to determine the factors affecting the timely diagnosis of cancer and the role of primary care in this process. Research questions: What are the effects of primary care and other effective factors in the cancer diagnosis process? Method: Our research has conducted in various outpatient clinics of Marmara Univercity Pendik Training and Research Hospital, between February 1 and May 31, 2019. Aged over 18 and diagnosed with cancer in the last six months included. The data collected through a questionnaire, by face-to-face interview. Results: 176 patients with a mean age of 55 participated, 45% of them stated that they applied to the primary care first when they had a complaint. Median time between first recognizing the sypmtoms to admission was 30 days. 45% of the patients stated that they waited for the symptoms to go away on their own. The mean time from the first suspicion of cancer to diagnosis was 39.7 days.19% of them stated that they applied to primary care with the symptoms that were present at the time of diagnosis. There was no significant difference between the diagnostic interval and diagnosis stage and the health institution patients first applied. Conclusions: There is no referral system in our country, patients can apply to any health institution. In our study, there was no relationship between admission steps and early diagnosis. Primary care has a significant advantage in the early diagnosis of cancer with its accessibility and holistic approach, its role in this field needs to be increased.
Keywords: Tıp; Dahili Tıp Bilimleri; Aile Hekimliği; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Family Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; SAĞLIK BAKIM BİLİMLERİ VE HİZMETLERİ; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; HEALTH CARE SCIENCES & SERVICES; MEDICINE, GENERAL & INTERNAL; Tıbbi Terminoloji; Tıbbi Sekreterlik ve Transkripsiyon; Sağlık Bilgi Yönetimi; Sağlık Meslekleri (çeşitli); Genel Sağlık Meslekleri; Gözden Geçirme ve Sınav Hazırlığı; Patofizyoloji; Liderlik ve Yönetim; Temel Bilgi ve Beceriler; Toplum Sağlığı ve Evde Bakım; Bakım Planlaması; Değerlendirme ve Teşhis; Dahiliye; Sağlık Politikaları; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; Medical Terminology; Medical Assisting and Transcription; Health Information Management; Health Professions (miscellaneous); General Health Professions; Review and Exam Preparation; Pathophysiology; Leadership and Management; Fundamentals and Skills; Community and Home Care; Care Planning; Assessment and Diagnosis; Internal Medicine; Health Policy; Family Practice; Medicine (miscellaneous); General Medicine